In-situ TEM study on the evolution of dislocation loops and bubbles in CeO2 during Kr+ single-beam and Kr+-H2+ dual-beam synergetic irradiation. (1st October 2022) - Cao, Ziqi; Ran, Guang; Wang, Zhen; Li, Yipeng; Wu, Xiaoyong; Wu, Lu; Huang, Xiuyin; Mo, Huajun
Highlights: Loop evolution during Kr + & H2 + dual- and Kr + single- beam irradiation was studied in-situ . Habit plane rotation of dislocation loop was found in CeO2 for the first time. Rafted loops were reported in CeO2 under Kr + & H2 + dual-beam irradiation for the first time. Change of Burgers vectors of PDLs in CeO2 were found for the first time. Average size and number density of loops and bubbles vs. dose were constructed. Abstract: CeO2 is widely used as the nonradioactive surrogate fuel of UO2 when studying the irradiation performance of UO2 . The evolution and characteristics of dislocation loops and bubbles in CeO2 foils were studied by in-situ transmission electron microscopy (TEM) observation during 400 keV Kr + & 30 keV H2 + dual-beam synergetic irradiation and 400 keV Kr + single-beam irradiation at 1073 K. The rotation of the habit plane of dislocation loops induced by above ion irradiation was found in the CeO2 for the first time, such as from [ 2 ¯ 1 1 ¯ ] to [ 3 ¯ 1 1 ¯ ] and then to [ 1 ¯ 00]. The rafted loops were first observed under Kr + & H2 + dual-beam synergetic irradiation, which not only had similar [ 1 ¯ 1 1 ¯ ] direction, but also belonged to perfect dislocation loops (PDLs). The rafted loops were formed not only by the growth of loops that absorbed irradiation defects, but also by the combination of loops. But, this phenomenon of loop rafting was not obvious during Kr single-beam irradiation. It was first found that Kr + irradiation induced the change of Burgers vectors of PDLs. The absorption of large PDLs to small PDLs was also observed. The average size and areal number density of dislocation loops and gas bubbles as a function of irradiation dose were constructed, which showed that the addition of H2 + obviously affected the characteristics of dislocation loops and gas bubbles and the swelling of CeO2 .